2019
DOI: 10.1111/1471-0528.16045
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic splitting following embryo biopsy: a cohort study of 207 697 single‐embryo transfers following IVF treatment

Abstract: Objective To evaluate the risk of monozygotic splitting with embryo biopsy during in vitro fertilisation (IVF). Design A cohort study. Setting Anonymised assisted reproductive technology national data from the Human Fertilisation and Embryology Authority, UK. Population Women undergoing single‐embryo transfer (SET) following either pre‐implantation genetic testing (PGT) involving embryo biopsy or IVF without PGT. Methods Data on women undergoing SET either following PGT and non‐PGT IVF treatment in 2000–2016 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…While the common practice of transferring multiple embryos to increase pregnancy chances is widely known to increase the incidence of dizygotic twins in ART pregnancies, a definitive mechanism to explain the association between ART and MZ twinning remains elusive. Several associations have been drawn in attempts to tease out the cause of MZ twinning in ARTs; prolonged in vitro culture (Liu et al ., 2018a) and embryo biopsy (Kamath, Antonisamy & Sunkara, 2020; Sellers et al ., 2020), as well as maternal age (Liu & Shi, 2021), have been put forward as risk factors. Curiously, MZ twinning appears to be more likely when transferring blastocysts versus cleavage‐stage embryos (MacKenna et al ., 2020).…”
Section: Monozygotic Twinning and Embryo Splittingmentioning
confidence: 99%
“…While the common practice of transferring multiple embryos to increase pregnancy chances is widely known to increase the incidence of dizygotic twins in ART pregnancies, a definitive mechanism to explain the association between ART and MZ twinning remains elusive. Several associations have been drawn in attempts to tease out the cause of MZ twinning in ARTs; prolonged in vitro culture (Liu et al ., 2018a) and embryo biopsy (Kamath, Antonisamy & Sunkara, 2020; Sellers et al ., 2020), as well as maternal age (Liu & Shi, 2021), have been put forward as risk factors. Curiously, MZ twinning appears to be more likely when transferring blastocysts versus cleavage‐stage embryos (MacKenna et al ., 2020).…”
Section: Monozygotic Twinning and Embryo Splittingmentioning
confidence: 99%
“…89 Moreover, risk increases after embryo biopsy, in which a recent study identified an increase from 1.5% in non-PGT-A cycles to 2.4% after PGT-A cycles. 90 Optimizing pregnancy rates may not only have psychological and economic benefits, 91 but it could also reduce graft longevity and therefore cumulative immunosuppression exposure. Published reproductive outcomes following UTx remain limited, with most studies awaiting pregnancy or livebirth before reporting.…”
Section: Conceptionmentioning
confidence: 99%
“…In addition, also a systematic review, pooling results from four studies, reported no increased risk of monozygotic twinning after PGT as compared with IVF without PGT [144]. However, Kamath et al [145] evaluated data from 207,697 SET cycles being performed mainly in women aged <35 years with no infertility diagnosis; many of the cycles were performed as part of a PGT-M or PGT-SR program. There was a significantly higher risk of zygotic splitting with PGT versus non PGT IVF cycles (2.4% vs. 1.5%), even after adjustment for potential confounders.…”
Section: Pgt In a Good-prognosis Patients Undergoing Setmentioning
confidence: 99%